On the interaction of social affect and cognition: empathy, compassion and theory of mind. (February 2018) - Preckel, Katrin; Kanske, Philipp; Singer, Tania
Highlights: Socio-affective and socio-cognitive processes are separable; behaviorally and neurally. The related neural networks co-activate and interact in complex social situations. Prosocial behavior necessitates both socio-affective and socio-cognitive functions. Abstract : Empathy, compassion and Theory of Mind (ToM) are central topics in social psychology and neuroscience. While empathy enables the sharing of others' emotions and may result in empathic distress, a maladaptive form of empathic resonance, or compassion, a feeling of warmth and concern for others, ToM provides cognitive understanding of someone else's thoughts or intentions. These socio-affective and socio-cognitive routes to understanding others are subserved by separable, independent brain networks. Nonetheless they are jointly required in many complex social situations. A process that is critical for both, empathy and ToM, is self-other distinction, which is implemented in different temporoparietal brain regions. Thus, adaptive social behavior is a result of dynamic interplay of socio-affective and socio-cognitive processes.